On the fly negotiation for urgent service level agreement on intercloud environment - Mehdi, Nawfal A.; Mamat, Ali; Ibrahim, Hamidah; K. Subramaniam, Shamala (Science Publications, 2011)
Problem statement: Impatient jobs are the jobs that have strict constraints in starting and completion time and need a fast response and attention in mapping to resources. The negotiation process in cloud computing needs a customer-provider agreement that leads to loss of a significant amount of time for impatient jobs. The huge increasing in cloud service providers makes selecting the best provider an exhaustive task. Approach: We considered the problem of Service Level Agreement (SLA) negotiation and commitment process for immediate mode scheduling under intercloud paradigm. This study explored an alternative model dedicated for impatient jobs under intercloud paradigm. We developed a model of negotiation where the cloud-broker had the ability to nominate the best cloud provider, commit the agreement and submit the jobs for execution. Cloudsim simulators with synthetic datasets had been used to evaluate the proposed system. Results: The results showed an improvement in SLA waiting time and the number of jobs failure. Conclusion: This study proved the importance of rapid mapping for impatient jobs in increasing system throughput.